Project-Based Learning Model Oriented Towards Creative Character in Poetry Text Learning for 10th Grade High School Students - Fufu Fadilah; Abdul Rozak; Dede Endang Mascita (International Journal of Educational Research Excellence (IJERE), 2024)
This research is entitled "Project-Based Learning Model Oriented Towards Creative Character in Poetry Text Learning for 10th Grade High School Students." Based on the results of research on poetry text learning activities, teachers need to adapt the learning model to effectively implement classroom activities. Therefore, the problem addressed by this research is how to model a creative character-oriented project-based learning approach in teaching poetry texts in 10th-grade high school. The aim of this research is to explain a creative character-oriented project-based learning model for teaching poetry texts. The research method used is Research and Development (RnD). The primary data source comes from expert teachers who validate the Learning Implementation Plan tool. Data collection is conducted by providing a set of question instruments to the validators for assessment. The data analysis technique involves validation analysis and effectiveness analysis, assisted by statistical analysis using Microsoft Excel. The presentation of the collected data includes a narrative description of the Learning Implementation Plan (RPP) after validation by the validators. Conclusions are drawn from the validation results based on questionnaire evidence provided by the three validators. At the final stage, after the lesson plan has been validated, it will be concluded and described. The research results showed that the average score before using the project-based learning model (O1) was 79.80. After using the project-based learning model, the score (O2) increased to 87.30. Data based on regression statistical tests using Microsoft Excel show that the p-value is < 0.005, indicating that H0 is accepted. This data explains that with a p-value of 0.868, there is a significant difference in learning outcomes between before and after using the Project-Based Learning Model.